PERAN MEDIA SOSIAL DALAM MENGEMBANGKAN LEMBAGA DAKWAH KAMPUS (LDK) UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA - Nenden Hopipah (Mudabbir: Jurnal Manajemen Dakwah, 2022)
Da'wah is important for every Muslim. However, as the times progressed, da'wah was also forced to adapt to it. This is because the target of da'wah considers 'old-fashioned' and monotonous if there is no renewal in the method of preaching. This research focuses on the role of social media in developing Da'wah Institutions at UIN Syarif Hidayatullah Jakarta campus. The methodology used in this research is descriptive quantitative to describe and determine the role of social media on the development of da'wah institutions. This research consists of primary data and secondary data. Primary data were obtained from survey results or the results of purposively distributing questionnaires from students, LDK members and LDK UIN Jakarta administrators, then conducting in-depth interviews with the daily administrators of the Campus Da'wah Institute (LDK) UIN Jakarta. While secondary data was obtained from social media LDK UIN Jakarta, articles from the internet, magazines, journals and newspapers. The results of the study show that, overall, from several parameters taken, that social media plays a very important role in developing LDK UIN Jakarta both in cadre, work programs, and so on.